2010
DOI: 10.1530/eje-09-0559
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal crisis in treated Addison's disease: a predictable but under-managed event

Abstract: Context: Adrenal crisis is a life-threatening event that occurs regularly in Addison's patients receiving standard replacement therapy. Patient reports suggest that it is an underestimated and undermanaged event.Objective: To assess the frequency of adrenal crisis in diagnosed patients and to understand the factors contributing to the risks of adrenal crisis. Design: We conducted a postal survey of Addison's patients in four countries, UK (nZ485), Canada (nZ148), Australia (nZ123) and New Zealand (nZ85) in 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
141
3
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 133 publications
(162 citation statements)
references
References 17 publications
17
141
3
1
Order By: Relevance
“…( Table 3), [15][16][17][18] greater than other infections or febrile illnesses. This is likely because it directly affects the intestinal absorption of glucocorticoids taken orally.…”
Section: Clinical Significancementioning
confidence: 99%
See 4 more Smart Citations
“…( Table 3), [15][16][17][18] greater than other infections or febrile illnesses. This is likely because it directly affects the intestinal absorption of glucocorticoids taken orally.…”
Section: Clinical Significancementioning
confidence: 99%
“…[15][16][17] These estimates were based on retrospective studies using questionnaires, and limited by reporting bias. A recent prospective study 18 found 64 episodes of adrenal crisis in 423 patients with primary and secondary adrenal insufficiency (8.3 adrenal crises/100 PYs), and, alarmingly, 4 adrenal crisis-related deaths were noted over a follow-up period of 2 years (0.5 adrenal crisis-related deaths per 100 PYs).…”
Section: Definition and Epidemiologymentioning
confidence: 99%
See 3 more Smart Citations